Changing Political Regimes and Performance of the Nairobi Securities Exchange - Musimbi, David (My University, 2014)
The stock market all over the world play a critical role as one of the most sensitive indicators of the business cycle and one of the most influential variables in. the government index of leading economic indicators. Companies quoted on the Nairobi Securities Exchange have been undergoing turbulent times due to fluctuation in the prices of shares, consequently affecting investors either way and hence making them uncertain about the future. This study, first sought to evaluate the effect that political regime changes have on returns that investors get on Nairobi Securities Exchange. Secondly, the study determined the effect of political regime change across different market segments. Published time series quarterly data was sourced from the Central Bank of Kenya. Kenya National Bureau of Statistics and Nairobi Securities Exchange data bases. In order to achieve all the specific objectives a regression model, and threshold generalized autoregressive conditional heteroscedasticity models were used to ascertain the volatility of stock returns. Empirical results of the regression model revealed that there was a weak relationship between changing political regimes and the performance of the NSE. Also the study found out that different political variables affect different market segments differentl y.